(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kravtsova A. Pedagogical faculty students training in schoolchildren organization of group forms learning. The article deals with the problem concerning Pedagogical faculty students training in schoolchildren organization of group forms learning. Group activities stimulates individualization in the process of learning, guarantees the use of knowledge in full, increases one’s responsibility for final results of learning material.